(untitled) (Historia, 2021)
Conceptualised in 1933, the Jan Hofmeyr Improvement Scheme was Johannesburg (and South Africa’s) first subsidised municipal housing development for the white poor. Being a slum clearance intervention, its design was informed by the modernist imaginary of rational city planning and the social reformist aspirations of a “garden city”-style working class housing in metropolitan cities. Linked to Susan Parnell’s seminal work on the crucial connection between slum clearance, council housing provision and racial segregation in Johannesburg, this is a micro-level analysis of the origins and completion of the Jan Hofmeyr scheme and the civic social imaginaries that shaped it. Focusing on the bureaucratic and political sections of the local state in relation to the Public Health Committee (PHC), it is argued that the city’s medical officer of health (MOH), Dr H.L. Milne and Lionel Leveson, a city councillor, each brought a distinctive vision to the project, a vision that was also shaped by civil society organisations. The scheme became important as signifier of the city’s racial modernity. Over the period of its construction, a shift took place in the PHC from bureaucratic concern with housing, linked to sanitation, hygiene, and racial segregation, to the incorporation of a welfarist function at local state level. Soon after completion of this project, the city abandoned sub-economic housing schemes. Socio- politically, the site of the Jan Hofmeyr scheme led to the expansion and consolidation of a white Afrikaner welfare node to the west of the city, with a gradual but sure “whitening out” through forced removals of the broader area. Thus the foundations were laid for the later centrality of the area, and the Jan Hofmeyr township itself, to the Afrikaner Nationalist social imaginary. Efforts to uplift poor and working class white Afrikaners were concentrated here until well into the early 1990s.